The Interaction of Digital Transformation, Innovation And Environmental Uncertainty on Organizational Resilience - DIAB GHIZLANE (Communications of International Proceedings, 2022)
Organizations are forced to develop their resilience to be successful and survive in the market, especially in a highly uncertain environment. The key way to improve organizational resilience is digital transformation, widely considered and analyzed in the scientific and business environment. Similarly, to achieve organizational resilience, as previous research has argued, innovation in values, processes and organizational behaviors is necessary. However, it is important to note that the existing literature does not explore the mechanisms of how the interactions of digital transformation, broadly understood innovations of enterprises operating in a highly uncertain environment affect organizational resilience. For this purpose, this paper uses a fuzzy set qualitative comparative analysis (fs/QCA) methodological approach. The results indicate that there are three equifinal configurations for achieving organizational resilience: (1) digital transformation, exploratory innovation and technical uncertainty; (2) digital transformation, exploitative innovation and market uncertainty and (3) exploitative innovation, exploratory innovation, technical and market uncertainty. The paper concludes by highlighting the importance of practical relevance for companies to successfully execute digital transformation and further achieve organizational resilience.
Keywords: digital transformation; ambidextrous innovation; environmental uncertainty; organizational resilience; fs/QCA.